Nahwu Science and the Truth in Perspective of the Philosophy of Science - Massofia, Fitrah Dinanti; Maisarah, Imas; Shomadiyah, Wardatus; Ramadhan, Muhammad Fadli (Al-Fusha : Arabic Language Education Journal, 2024)
Nahwu science is a science that discusses the rules of the Arabic language. However, there is little doubt when Nahwu science is viewed from an academic perspective which requires an epistemological aspect. So that in seeking the truth of a science, it is discussed in the study of the philosophy of science. The purpose of this study is to examine how the science of nahwu and its truth in the philosophy of science. This study is qualitative research with library research approach. Data collection techniques use literature studies from books, articles, and scientific journals. The results showed that Nahwu science is true as a science based on the Coherence Theory of Truth in the philosophy of science. So this is answered as proof that “Nahwu science is a science” so that Nahwu science is not only considered a tool in Arabic, but knowledge in Islamic and general education.